Global contact lens prescribing 2000-2020 - Morgan, Philip B; Efron, Nathan (Clinical and experimental optometry, 2022)
Contact lens prescribing data serve as a benchmark for eye care clinicians in assessing their own prescribing patterns and provide useful contextual information for researchers and the contact lens industry. To document global trends in contact lens prescribing during the first two decades of this century. A longitudinal survey of contact lens prescribing was conducted by asking contact lens practitioners to provide 11 items of information from 10 consecutive contact lens fits between January and March each year from 1996 to 2020, inclusive. Data relating to 406,859 contact lens fits were collected from 71 countries between 1996 and 2020, generating 4.5 million data points. Demographic analysis for 61 nations returning ≥100 fits demonstrated that a majority of lenses (65-70%) were fitted to females. The average age of lens wearers was 30.8 ± 13.9 years for males and 32.5 ± 14.3 years for females. Trend analysis of 20 countries returning prescribing data for ≥13 years between 2000 and 2020 revealed the following: increase in the age of lens wearers; dramatic rise in the extent of fitting silicone hydrogel and daily disposable lenses; increased fitting of soft toric and multifocal lenses; increasing proportion of rigid lens fits in specialist (non-spherical) designs; incomplete provision of near contact lens corrections for contact lens wearing presbyopes; ongoing low levels of extended wear fits; and almost exclusive use of multi-purpose care systems. Daily disposable lenses were used for both full-time and part-time wear, whereas rigid and soft reusable lenses were primarily worn full time. The evolution of international contact lens fitting over the first two decades of this century is documented. The data presented here may assist all stakeholders in advancing contact lens clinical practice, informing contact lens research, and guiding contact lens manufacturers.